Photovoltaic response promoted via intramolecular charge transfer in pyrazoline-based small molecular acceptors: Efficient organic solar cells - Muhammad Khalid; Ayesha Mustafa; Sarfraz Ahmed; Muhammad Adnan Asghar; Tansir Ahamad; Ataualpa A.C. Braga; Suvash Chandra Ojha (Arabian Journal of Chemistry, 2023)
Herein, a series of pyrazoline based non-fullerene compounds (THP1-THP8) having ladder-like backbone was designed by structural modulation with various electron accepting moieties. The density functional theory (DFT) and time-dependent functional theory (TD-DFT) study was executed at M06/6-311G(d,p) level for structural optimization and to determine the electronic and optical characteristics of the pyrazoline based chromophores. The optimized structures were employed to execute frontier molecular orbital (FMO), transition density matrix (TDM), density of state (DOS), open circuit voltage (Voc) and reorganization energy analyses at the aforementioned level of DFT to comprehend the photovoltaic (PV) response of THP1-THP8. The red-shifted absorption spectrum (512.861–584.555 nm) with reduced band gap (2.507–2.881 eV) allow considerable charge transferal from HOMO to LUMO in all the studied compounds. Global reactivity parameters (GRPs) demonstrated high softness with considerable reactivity in THP1-THP8. Moreover, remarkable Voc values (2.083–2.973 V) were noted for all the derivatives (THP1-THP8). However, THP2 with lowest energy gap (2.364 eV), highest λmax (617.482 nm) and softness (0.423 eV) values is considered good candidate among afore-said chromophores. Hence, the studied chromophores with efficient properties are appropriate for experimentalists in terms of manufacturing of efficient OSCs.